Materials characterization and mechanical properties of graded tool steels processed by a new co‐spray forming technique. Issue 8 (6th August 2014) - Cui, C.; Schulz, A.; Uhlenwinkel, V.
<x xml:space="preserve">Abstract</x> In order to meet the requirements of micro cold forming tools, a new co‐spray forming process has been applied to produce graded materials from two different tool steels in this study. The two steel melts were atomized and co‐sprayed simultaneously onto a flat substrate, resulting in a flat graded deposit when the two sprays were overlapped. To eliminate porosity and break up carbide network, the graded deposits were further hot rolled. The resultant graded tool steels were investigated with respect to porosity, element distribution, microstructure, hardness, strength, and toughness. The degree of overlapping of the two sprays determined the concentration gradient of the chemical elements in the deposits. The overlapping of the spray cones also contributed to low porosity in the gradient zone of the deposits. The porosity in the graded deposits could be essentially eliminated by means of hot rolling. The carbides and grain structures of the hot rolled tool steels were fine and homogeneous. By means of combining different tool steels in a single deposit, different microstructures and properties were combined.